2021
DOI: 10.3389/fphys.2021.738333
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training and Circulating Small Extracellular Vesicles: Appraisal of Methodological Approaches and Current Knowledge

Abstract: In response to acute exercise, an array of metabolites, nucleic acids, and proteins are enriched in circulation. Collectively termed “exercise factors,” these molecules represent a topical area of research given their speculated contribution to both acute exercise metabolism and adaptation to exercise training. In addition to acute changes induced by exercise, the resting profile of circulating exercise factors may be altered by exercise training. Many exercise factors are speculated to be transported in circu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 108 publications
(251 reference statements)
0
31
0
Order By: Relevance
“…EVs offer a promising diagnostic potential for the beneficial effects of PA in organs beyond the skeletal muscle. 55,56 Investigating the aforesaid mechanisms in children would help to establish specific doses of PA that stimulate the autoimmune response but do not induce immune imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…EVs offer a promising diagnostic potential for the beneficial effects of PA in organs beyond the skeletal muscle. 55,56 Investigating the aforesaid mechanisms in children would help to establish specific doses of PA that stimulate the autoimmune response but do not induce immune imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that these enzymes may be released by damaged muscle [41][42][43] . The mechanism(s) by which the enzymes enter the blood may combine leakage through sarcolemma wounds, exocytosis, extracellular vesicles [44][45][46] and activity-dependent lymph flow 47,48 .…”
Section: Sarcolemma Damage In Exercisementioning
confidence: 99%
“…Exerkines are increasingly recognized as critical intermediaries of exerciserelated changes and health benefits, mainly due to their role in inter-organ and systemic communication and coordination. 5 Most of the literature associates the benefits of exerkines with aerobic exercise; 6 however, the effects of resistance or combined exercise (i.e., aerobic plus resistance training), intensity (i.e., light, moderate), length of program, frequency and/or duration of the session are less studied. 7 Furthermore, the relationship between exerkines and response in individuals with T2DM remains unexplored.…”
Section: Introductionmentioning
confidence: 99%